3(2x+3)=45

Simple and best practice solution for 3(2x+3)=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+3)=45 equation:


Simplifying
3(2x + 3) = 45

Reorder the terms:
3(3 + 2x) = 45
(3 * 3 + 2x * 3) = 45
(9 + 6x) = 45

Solving
9 + 6x = 45

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 6x = 45 + -9

Combine like terms: 9 + -9 = 0
0 + 6x = 45 + -9
6x = 45 + -9

Combine like terms: 45 + -9 = 36
6x = 36

Divide each side by '6'.
x = 6

Simplifying
x = 6

See similar equations:

| (2x+5)=27 | | (x-5)10+(1-2x)15=(3-x)14 | | x-12y=-36 | | 80-6x=7x+16 | | 7(9)+9y=63 | | 3y-5x=0 | | 3y+2(-3)=-6 | | (8x-8)/7-4(x+4)/7+7=8 | | x^2-24x-51=0 | | x^3-24x^2-51x=0 | | 15x+12y=13 | | 3x+33=11x-66 | | 1/5t-3=17 | | 9y-9y= | | 0=3t^2-16t+15 | | 0=3t^2+16t+15 | | c=(pi)10 | | y+6(-3)=9 | | -5n-1=-17+3 | | 8(b+3)=4b | | (5x+6)(2x-7)= | | y=20/3x-1 | | 1.5x-8.4=0.4+2.6x | | 3x(87*2)=0 | | 4x^2-19x+18=-6x+8 | | 20x-3y=1 | | x^2-x-16=-5x-4 | | 17x-13=-4x+47+15x | | 18x+125=12x+200 | | 18x=12x | | x+3x+15=0 | | 2cos^2=1+2sin^2x |

Equations solver categories